INCREASING COASTAL COMMUNITY AWARENESS REGARDING PERSONAL AND ENVIRONMENTAL HEALTH IN THE BINALATUNG AREA, PANTAI AMAL VILLAGE, TARAKAN CITY - Firdaus, Muhammad; Roem, Muhammad; Taqwa, Amrullah; Achyani, Ratno; Jabarsyah, Abdul; Rachmawani, Dori; Laga, Asbar; Wiharyanto, Dhimas; Irawati, Heni; Salim, Gazali; Alawiyah, Tuty; Haryono, M Gandri; Gaffar, Syamsidar; Yushra, Yushra; Yusuf, Muhammad Yusfi; Muhtar, Dian Islamia; Romdoni, Taufiq Ahmad; Kase, Ardy Andreas Bernard (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2025)
Abstract Binalatung area in Pantai Amal Subdistrict is a coastal zone that has developed as a seaweed cultivation center and tourist destination in Tarakan City. However, the economic growth and settlement expansion in this region are not yet balanced with public awareness of environmental health and sanitation. This community engagement program aimed to raise awareness through health education, community discussion, and basic medical checkups for coastal residents. The methods involved coordination with local stakeholders, distribution of educational materials (brochures and posters), face-to-face discussions, and health services in collaboration with Pantai Amal Public Health Center. The results showed high community participation as reflected in enthusiasm during health consultations and discussions. These findings indicate that a collaborative and direct educational approach is effective in increasing public understanding of the connection between environmental conditions, personal health, and quality of life. This activity is expected to serve as a foundational intervention model for similar coastal communities. Keywords: environmental health, coastal community, sanitation, Binalatung   Abstrak   Wilayah Binalatung di Kelurahan Pantai Amal merupakan kawasan pesisir yang berkembang sebagai sentra budidaya rumput laut dan destinasi wisata Kota Tarakan. Namun, pertumbuhan aktivitas ekonomi dan pemukiman di wilayah ini belum diimbangi dengan kesadaran masyarakat terhadap pentingnya sanitasi dan kesehatan lingkungan. Kegiatan pengabdian ini bertujuan meningkatkan kesadaran masyarakat melalui sosialisasi, diskusi, dan pemeriksaan kesehatan dasar secara langsung kepada warga pesisir. Metode yang digunakan meliputi koordinasi dengan pemangku kepentingan lokal, distribusi media edukasi (brosur dan poster), diskusi tatap muka, serta layanan pemeriksaan kesehatan bekerja sama dengan Puskesmas Pantai Amal. Hasil kegiatan menunjukkan tingginya partisipasi masyarakat yang ditandai dengan antusiasme dalam mengikuti pemeriksaan dan diskusi kesehatan. Temuan ini mengindikasikan bahwa pendekatan kolaboratif berbasis edukasi langsung efektif dalam membangun pemahaman warga terhadap hubungan antara kondisi lingkungan dengan kesehatan pribadi dan kualitas hidup. Kegiatan ini diharapkan menjadi model intervensi awal yang dapat dikembangkan lebih lanjut untuk wilayah pesisir lainnya dengan karakteristik serupa.   Kata Kunci: kesehatan lingkungan, masyarakat pesisir, sanitasi, Binalatung